Brain MRI abnormalities and spectrum of neurological and clinical findings in three patients with proximal 16p11.2 microduplication. Issue 8 (28th May 2014) - Filges, Isabel; Sparagana, Steven; Sargent, Michael; Selby, Kathryn; Schlade‐Bartusiak, Kamilla; Lueder, Gregg T.; Robichaux‐Viehoever, Amy; Schlaggar, Bradley L.; Shimony, Joshua S.; Shinawi, Marwan
<x xml:space="preserve">Abstract</x> The phenotype of recurrent ∼600 kb microdeletion and microduplication on proximal 16p11.2 is characterized by a spectrum of neurodevelopmental impairments including developmental delay and intellectual disability, epilepsy, autism and psychiatric disorders which are all subject to incomplete penetrance and variable expressivity. A variety of brain MRI abnormalities were reported in patients with 16p11.2 rearrangements, but no systematic correlation has been studied among patients with similar brain anomalies, their neurodevelopmental and clinical phenotypes. We present three patients with the proximal 16p11.2 microduplication exhibiting significant developmental delay, anxiety disorder and other variable clinical features. Our patients have abnormal brain MRI findings of cerebral T2 hyperintense foci (3/3) and ventriculomegaly (2/3). The neuroradiological or neurological findings in two cases prompted an extensive diagnostic work‐up. One patient has exhibited neurological regression and progressive vision impairment and was diagnosed with juvenile neuronal ceroid‐lipofuscinosis. We compare the clinical course and phenotype of these patients in regard to the clinical significance of the cerebral lesions and the need for MRI surveillance. We conclude that in all three patients the lesions were not progressive, did not show any sign of malignant transformation and could not be correlated to specific clinical features. We discuss potential etiologic mechanisms that may include overexpression of genes within the duplicated region involved in control of cell proliferation and complex molecular mechanisms such as the MAPK/ERK pathway. Systematic studies in larger cohorts are needed to confirm our observation and to establish the prevalence and clinical significance of these neuroanatomical abnormalities in patients with 16p11.2 duplications. © 2014 Wiley Periodicals, Inc.